Clinical analysis of 45 cases of perforation were identified during endoscopic retrograde cholangiopancreatography procedure - Miao, Yin-Shui; Li, Yuan-Yuan; Cheng, Bo-Wen; Zhan, Yan-Fang; Zeng, Sheng; Zhou, Xiao-Jiang; Chen, You-Xiang; Lv, Nong-Hua; Li, Guo-Hua (Frontiers in Medicine, 2022)
Background Endoscopic retrograde cholangiopancreatography (ERCP) has become an important method to diagnose and treat biliary-pancreatic diseases. Perforations are infrequent but serious complications can occur during ERCPs. However, it is unclear which patients are suitable for surgery and when these patients should receive surgery. Aim To analyze the outcome of 45 patients with endoscopic retrograde cholangiopancreatography (ERCP) related perforation. Materials and methods We retrospectively reviewed all 45 patients with ERCP-related perforation between January 2003 and December 2017, and observed the location and causes of perforation, treatment strategies, and mortality. Results Twenty thousand four hundred and seventy-nine patients received ERCP procedures from January 2003 to December 2017 in our digestive endoscopy center. Forty-five patients suffered from ERCP-related perforations. The incidence rate of ERCP-related perforations was 0.22%. Twenty-six patients suffered from periampullary perforations, 15 patients suffered from duodenal wall perforations, 1 patient suffered from a fundus perforation, 1 patient suffered from a residual gallbladder duct perforation, 1 patient suffered from a papillary diverticulum perforation, and 1 patient suffered from an intrahepatic bile duct perforation. Six patients with duodenal perforations underwent surgery, and the other patients received conservative treatment. One patient with a duodenal perforation and ERCP-related pancreatitis died of heart failure, and all the other patients recovered. The mortality rate was 2.2%. Conclusion Endoscopic closure is seen as the first method for treating Stapfer type I perforations in the early phase, and surgery is seen as a remedial method when local treatment was failed. The Stapfer type II to type IV perforations can recover by conservative treatment.